Extracção sequencial em sedimentos e resíduos da antiga mina da Tinoca: geoquímica mineralogia - Morais, C. (2012)
Mine wastes and sediments from the ancient copper mine of Tinoca (Alto Alentejo – Portugal) were submitted to a sequential extraction with the objective to establish distribution patterns for copper (Cu), iron (Fe), zinc (Zn) and lead (Pb) in different specific phases: amorphous oxides; rystalline oxides; sulphides and silicates. The results of the sequential extraction showed that Cu and Fe were predominantly concentrated in the fractions: iron amorphous oxides and iron crystalline oxides. However, Zn was specially associated with silicates fraction. For Pb, the distribution pattern among the several geochemistries fractions was very heterogeneous. Analyses made by X-rays (DRXD) showed that tailings waste as well as the sediments are constituted essentially by quartz, phylossilicates and secondary inerals resultants of the lteration/oxidation metallic sulphides, namely, jarosite,goetite and ferrihidrite.